2020
DOI: 10.1186/s12974-020-1724-9
|View full text |Cite
|
Sign up to set email alerts
|

A comparison study of metabolic profiles, immunity, and brain gray matter volumes between patients with bipolar disorder and depressive disorder

Abstract: Background: Previous individual studies have shown the differences in inflammatory cytokines and gray matter volumes between bipolar disorder (BD) and unipolar depression (UD). However, few studies have investigated the association between pro-inflammatory cytokines and differences in brain gray matter volumes between BD and UD. Methods: In this study, 72 BD patients and 64 UD patients were enrolled, with comparable gender and age distributions (33.8% males and an average age of 39.3 ± 13.7 years). Each partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 69 publications
(79 reference statements)
5
35
0
1
Order By: Relevance
“…The fusiform gyrus and the lingual gyrus, as the same as the inferior temporal lobe, are also involved in visual processing. Gray matter volume reductions in these two regions have been reported in both this present research and previous studies [13,[82][83][84][85]. And the precuneus is a part of the parietal lobe, which involves a variety of complex functions, including recollection and memory, integration of information relating to the perception of the environment, episodic memory retrieval, and affective responses pain.…”
Section: Discussionsupporting
confidence: 83%
“…The fusiform gyrus and the lingual gyrus, as the same as the inferior temporal lobe, are also involved in visual processing. Gray matter volume reductions in these two regions have been reported in both this present research and previous studies [13,[82][83][84][85]. And the precuneus is a part of the parietal lobe, which involves a variety of complex functions, including recollection and memory, integration of information relating to the perception of the environment, episodic memory retrieval, and affective responses pain.…”
Section: Discussionsupporting
confidence: 83%
“…Recent structural MRI studies showed that IL-8 was associated with reduced gray matter volumes (GMV) in the left OFC in schizophrenia [91] and bilateral hippocampus in old rhesus macaques [89], which implicated in ammation might contribute to structural abnormalities. Another structural MRI study showed that GMV in the precentral gyrus negatively correlated with pro-in ammatory cytokine levels in BD patients [92], further supporting the idea that in ammation might contribute to structural abnormalities in the right precentral gyrus. A diffusion tensor imaging study found that higher levels of IL-8 were associated with lower fractional anisotropy values across the brain including the corticospinal tract [93], which suggested in ammation might contribute to white matter abnormalities and possibly impair the neural function of the precentral gyrus, for the reason that outputs of voluntary movements are controlled by the precentral gyrus through the corticospinal tract [94].…”
Section: Correlation Between Fc In the Right Precentral Gyrus And Il-mentioning
confidence: 80%
“…Recently, studies found that in ammation could affect cortical reward and motor circuits and was related to such symptoms (anhedonia and motor slowing) in psychiatric diseases such as BD [19,44,45]. Also, a recent neuroimaging study found abnormalities of brain regions in SMN correlated with in ammation in BD patients [46].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with BD show high levels of soluble IL-6 receptors and TNF receptors in serum samples [ 207 ], and the levels of proinflammatory cytokines have been correlated to the reduction of gray matter volume [ 207 ]. Maternal inflammation during the third trimester of pregnancy increased the plasma concentration of IL-6, TNF-α, and CCL2, and the rate of the attention-deficit hyperactivity disorder of the birthed children [ 208 ]. Thus, many current studies suggest the risk of aberrant immunity on the emergence of psychosis symptoms.…”
Section: Main Textmentioning
confidence: 99%